P1285ACTIVE FLUID MANAGEMENT IMPROVES LEFT VENTRICULAR FUNCTION AND MECHANICS IN HEMODIALYSIS PATIENTS: A RANDOMIZED TRIAL. (6th June 2020) - Paunic, Zoran; Dekleva-Manojlovic, Milica; Markovic-Nikolic, Natasa; Dimkovic, Nada
Abstract: Background and Aims: Relative hypervolemia or overhydration (ROH) above 15% of the normally hydrated body extracellular volume (ECV), assessed by bioimpedance spectroscopy (BIS), puts chronic hemodialysis (HD) patients at an increased risk of cardiovascular (CV) incidents and death, as numerous studies have shown. It has also been reported that the reduction of ROH to the value below 15% of ECV can positively affect hypertension and some aspects of the left ventricle (LV) function and morphology. The concept of Active Fluid Management (AFM) has been developed and it hypothesized that maintaining average (weekly) predialysis overhydration (AWOH) below 15% of ECV will preserve heart function and structure and thus lead to fewer CV complications. The purpose of this study was to investigate the effects of AFM concept guided by BIS on cardiac morphology, mechanics and function in chronic HD patients. Methods: Randomized prospective single-center study lasted 9 months and included BIS naive HD patients from the Dialysis unit of Zvezdara University Medical Center in Belgrade with HD vintage greater of 3 months. BIS was performed by Body Composition Monitor (BCM). In accordance with the AFM concept, BIS was applied to patients in the Active group every time their average weekly ROH (AWOH) exceeded 15% of their normal ECV and their dry weight (DW) was time-adjusted according to the findings along with clinical assessment. In the Control group, patients were treated in accordance with the standard clinical practice. Cardiac structural and functional characteristics were obtained at the beginning and the end of the study by using 2-dimensional Doppler echocardiography and spackle tracking modality. Cardiac markers (high-sensitivity C-reactive protein, Troponin T and N-terminal pro-brain natriuretic peptide) were measured at the same time. Results: The study included 42 patients (25 M) in the Active group and 41 patients (23 M) in the Control group. Patients from both groups were of similar age (56.1 ± 11.5 vs. 57.5 ± 13.2 years, p = 0.6) and HD vintage (79.9 ± 59.2 months vs. 95.3 ± 80.0 months, p = 0.6). 73 patients completed the 9 months study, 38 in the Active group and 35 in Control group. Within the Active group, recommended AWOH lower than 15% ECV has 55% at start and 76% of patients at the end of study (p< 0.01). In parallel, there were improvements in their LV ejection fraction (LVEF), from 41.3 ± 9.3% to 44.0 ± 8.8% (p < 0.01), LV end systolic volume index, from 40.2 ± 12.5 to 35.8 ± 13.5 ml/m 2 (p < 0.05), LV mass indexed at height at 2.7 (LVMI 2.7 ) from 62.8 ± 19.7 g / m 2.7 to 57.7 ± 16.9 g/m 2.7 (p <0.01) and Global radial strain (GRS) - from 18.6 ± 10.2% to 21.8 ± 12.2% (p <0.05). In the Control group, there were signs of LV diastolic function worsening at the end of the study: E/A ratio increased from 1.0 ± 0.3 to 1.2 ± 0.6 (p < 0.01), as well as E/e' lateral ratio from 10.6 ± 5.0 to 11.1 ±4.1 (p <0.01) and right ventricle systolic pressure (RVSP) from 34.8 ± 10.2 mmHg to 38.8 ± 8.3 mmHg (p <0.05). This worsening of LV diastolic function in the Control group correlated with the increased level of one of the cardiac markers, N-terminal pro-brain natriuretic peptide (NT-proBNP) - from 5810.0 (3339.0-15627.0) pg/ml to 8024.0 (4433.0-17467.0) pg/ml (p <0.04). Conclusion: Active Fluid Management leads to the improvement of left ventricle systolic function and prevents worsening of diastolic function in the observed hemodialysis patients. This concept implemented could favourably affect the clinical course of hemodialysis patients in daily clinical practice.